A CONTRIBUIÇÃO DO DIAGNÓSTICO ORGANIZACIONAL COMO FERRAMENTA PARA AUXILIAR NA TOMADA DE DECISÃO - Carvalho, Jorge Rodrigues de (2012)
In the globalized and competitive world, the constant and rapid changes are forcing organizations to increase their capacity to innovate through new skills and competencies to achieve their goals. Thus, organizational diagnosis was presented as a tool to assist the manager in decision making. The theoretical sought to base the defined problem and the issues addressed in the research through a deepening of themes, such as the definition of organizational diagnosis, management concepts, functions, roles, and skills and competence of the administrator / manager responsible for decision making, and as a link management models that influence the performance of organizations. In this context, the author highlights the role of quality as the motivating factor of modern management. These elements will mark out the research. The methodology used was a multiple case study, as several companies participated in the survey through interviews and documentary research. As a final conclusion which drew together the answer to the question-formulated problem can be stated that organizational diagnosis that is, in fact, an auxiliary tool for decision-making by administrators / managers. The analysis and discussion, from the responses tabulated and turned into graphics to better understand the results, evidenced by the behavior of respondents, organizational diagnosis that provides the evidence base through data and information for decision making safe, potentially providing a most appropriate decision for the organization.